IMPROVING MUNGGU VILLAGE'S HUMAN RESOURCE SUPPORTFOR TOURISM READINESS THROUGH â€œMUNGGU MIXERâ€ PROGRAM - Peter Wayan Minheer; Luh Putu Tri Karismawati; I Made Arya Bayu Suta; Ni Made Eripa Ordani Astuti; Putu Chris Susanto (LPPM Universitas Dhyana Pura, 2023)
Munggu Tourism Village in Mengwi District, Badung Regency, Bali has a variety of natural(beach) and cultural tourism potential. One of the obstacles faced is the uneven readiness ofhuman resources in this tourist village in serving tourists and producing creative productssupporting tourism.The students of Thematic Community Service Programof Dhyana PuraUniversity conducted Munggu Mixer activities aimed at increasing the capacity of traders atMunggu Beach in serving guests with hospitality standards and in English, increasingunderstanding and practice of sanitary hygiene of tourism actors in Munggu. Fromseveralactivities carried out, it was found that there was an increase in the percentageofunderstanding of Munggu Village tourism supporting human resources in Englishcommunication, Hygiene and sanitation, and business digitalization.